Real GDP growth rates of Singapore, Taiwan and Hong Kong: An asymmetric multivariate GARCH approach - Hai, V.T. (2014)
18th World IMACS Congress and MODSIM09 International Congress on Modelling and Simulation: Interfacing Modelling and Simulation with Mathematical and Computational Sciences, Proceedings